Long-term trends in international migration: lessons from macroeconomic model - Docquier, Frédéric D (Economics and Business Review, 2018)
In this paper I develop a stylized model of the world economy and use it toexplain the long-run trends in international migration. The model very well fits thetrends of the last 40 years which are mainly governed by the evolution of populationdisparities between industrialized and developing countries. Then I provide migrationprojections for the 21st century and show that future migration is also governedby socio-demographic changes. I predict a robust increase in immigration pressuresfrom sub-Saharan Africa and MENA countries to European countries.